Directions and Prospects for Educational Linguistics - Hult, Francis M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
(3z(BThis anthology is a testament to the vitality of Educational Linguistics and its transdisciplinary, problem-posing approach. With chapters ranging from the ethnopoetics of oral narrative to the use of eye-tracking technology to study recasts in CMC, this collection extends the boundaries of educational linguistics in significant, interesting, and innovative ways. In so doing, it will inspire much conversation about where this growing field is heading in the decades to come.(3y (BProfessor Diane Larsen-Freeman, University of Michigan, USA (3z(BThis edited collection provides us with a unique contribution as it demonstrates the applicability of a varied repertoire of innovative research methods to diverse language learning programs.(3y (BProfessor Elana Shohamy, Tel Aviv University, Israel (3z(BThis exciting collection includes original analyses of communicative actions and interactions in multiple international and multimodal settings to illustrate the promise of educational linguistics. A must-read for all those curious about contemporary applied linguistic scholarship and its pedagogical relevance.(3y (BProfessor Mary McGroarty, Northern Arizona University, USA (3z(BContributors to this volume have been in the vanguard of a bold, transdisciplinary movement that has re-tuned and reinvigorated the field of educational linguistics in ways that are uniquely suited to contemporary research on language in education. The chapters make challenging new research-theory-policy-practice connections and draw on cutting edge research$1 (Ba compelling read for both new and established researchers.(3y (BProfessor Marilyn Martin-Jones, University of Birmingham, UKs
Educational Linguistics: Working at a Crossroads -- Theme-Based Research in the Transdisciplinary Field of Educational Linguistics -- Methodology and Pedagogy in Educational Sociolinguistics: Researching and Teaching in Linguistically Diverse Schools -- Discourse Issues in Cross-Cultural Pragmatics: Educating the Community -- Communicative Competence Revisited: An Ethnopoetic Analysis of Narrative Performances of Identity -- Employing Eye-Tracking Technology in Researching the Effectiveness of Recasts in CMC -- The Educational Linguistics of Bilingual Deaf Education -- Multiuser Digital Games as Sites for Research and Practice -- Envoi: Towards Responsible Language Educational Management.
Keywords: Education; Applied linguistics; Language and languages; Education; Language Education; Applied Linguistics; Learning & Instruction